Animal Farming and Environmental Interactions in the Mediterranean Region 2012
DOI: 10.3920/978-90-8686-741-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature-humidity index (THI) on daily production of dairy cows in Mediterranean region in Croatia

Abstract: With the aim of analysis the influence of temperature-humidity index (THI) on daily performance of dairy cows in Croatian Mediterranean region, 217,509 test-day records collected from January 2005 until April 2010 were extracted from HPA (Croatian Agricultural Agency) database. Milk recording in Croatia occurs according to the alternative milk recording method every four weeks, therefore, daily production of milk yields and components was projected using projection parameters estimated in authors' earlier rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
1
18
1
Order By: Relevance
“…For a cow with access to shade, the daily fat yield would, thus, decrease by 8 g/day per unit increase of HLI. This decline is comparable with the decline of 10 g/day per unit increase of the HLI above 80 that Hammami et al (2013) found, but not as steep as the decline of 0.07% found by Gantner et al (2012) at daily THI ⩾ 72. On the other hand, cows with access to shade showed a less marked decrease of the milk protein content.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For a cow with access to shade, the daily fat yield would, thus, decrease by 8 g/day per unit increase of HLI. This decline is comparable with the decline of 10 g/day per unit increase of the HLI above 80 that Hammami et al (2013) found, but not as steep as the decline of 0.07% found by Gantner et al (2012) at daily THI ⩾ 72. On the other hand, cows with access to shade showed a less marked decrease of the milk protein content.…”
Section: Discussionsupporting
confidence: 80%
“…As HLI increased, after a lag-time of 3 days, the milk lactose production decreased by about 0.02% and the protein content decreased by about 0.01% per unit increase of HLI. This decline in protein content is less than the 0.06% decline reported by Gantner et al (2012) for cows in free-stall barns in Croatia. We demonstrated no unambiguous effect of shade on the relationship between HLI and milk composition.…”
Section: Discussioncontrasting
confidence: 55%
“…The standard lactation milk yield was 4 to 5% lower than that reported for the other calving seasons (Figure 2). Gantner et al [25] found that THI values often exceeded 72 in the three regions (eastern, Mediterranean, and central) of Croatia in spring and summer, during which cows tend to develop HS. During autumn and winter when THI values are typically lower than 72, cows rarely experience HS.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate changes in horn temperature during rumination, environmental temperature and relative humidity were combined to a temperature-humidity index (THI) score based on the following formula [64][65][66]:…”
Section: Hli and Thi Calculationmentioning
confidence: 99%